HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN DI PUSKESMAS TENAYAN RAYA PEKANBARU TAHUN 2024 - Yulnefia Yulnefia; Indah Dwi Lestari (Collaborative Medical Journal, 2024)
expectations, are requirements that must be met in order to provide satisfaction to service users. Problems with the quality of health services in Indonesia include a lack of evaluation of health services and satisfaction surveys that do not involve patients. Based on the results of the initial survey, the Tenayan Raya Community Health Center received Plenary Accreditation which has succeeded in improving and maintaining the quality of health services for patients. This study aims to determine the relationship between service quality and patient satisfaction at the Tenayan Raya Pekanbaru Community Health Center in 2024. This type of research is observational analytics using a cross-sectional research design. The sampling technique in this research is accidental sampling technique. This research was conducted at the Tenayan Raya Pekanbaru Community Health Center. Respondents were 290 patients at the General Poly, Obstetrics, Dental and Oral Polyclinics in February 2024. The results of the study show that there is a relationship between service quality and patient satisfaction at the Tenayan Raya Pekanbaru Community Health Center in 2024 with a p-value of 0.000 with a positive correlation direction. Therefore, it can be concluded that service quality has a relationship with patient satisfaction at the Tenayan Raya Pekanbaru Community Health Center in 2024.